1992
DOI: 10.1073/pnas.89.20.9744
|View full text |Cite
|
Sign up to set email alerts
|

Trisomy 7 and trisomy 10 characterize subpopulations of tumor-infiltrating lymphocytes in kidney tumors and in the surrounding kidney tissue.

Abstract: We performed conventional cytogenetic analysis and fluorescence in situ hybridization in short-term

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
19
2

Year Published

1993
1993
2015
2015

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 61 publications
(21 citation statements)
references
References 15 publications
0
19
2
Order By: Relevance
“…44 Loss of the Y chromosome and trisomy 7 were the most common abnormalities noted in benign prostatic hyperplasia, 45 although the authors point out the possibility that the trisomic cells may be infiltrating lymphocytes, which may have trisomy 7. 46 In our study, however, no lymphocytes or epithelial cells contaminated the fibroblast cultures.…”
Section: Discussioncontrasting
confidence: 49%
“…44 Loss of the Y chromosome and trisomy 7 were the most common abnormalities noted in benign prostatic hyperplasia, 45 although the authors point out the possibility that the trisomic cells may be infiltrating lymphocytes, which may have trisomy 7. 46 In our study, however, no lymphocytes or epithelial cells contaminated the fibroblast cultures.…”
Section: Discussioncontrasting
confidence: 49%
“…Alternatively, otherwise healthy people might have (numerical) chromosomal aberrations (18). Dal Cin et al (1992) reported on the occurrence and selective accumulation of apparently normal T-lymphocytes with trisomy 7 or 10 in patients with renal cell carcinoma (9). The practical consequences of these phenomena are that subsequent statistical decision procedures will lead to wrong decisions (Table 4).…”
Section: Discussionmentioning
confidence: 99%
“…Probes specific for chromosomes Nos. 1 , 7 , 8 , and 9 were used for estimation of ISH artiIn situ hybridisation (ISH) techniques are now widely applied in cytogenetic research and clinical diagnosis. Important features of the molecular ISH approach distinguishing it from morphological banding cytogenetic techniques are: (1) the possibility of interphase cell analysis or "interphase cytogenetics" (8); (2) unambiguous identification of marker chromosomes facts.…”
mentioning
confidence: 99%
“…17 evaluated the frequency of PTEN trisomy through in situ hybridization in 17 specimens of patients undergoing nephrectomy. Trisomy was found in five patients (30%).…”
Section: Results Results Results Resultsmentioning
confidence: 99%